Epithelial-Mesenchymal Transition Phenotype, Metformin, and Survival for Colorectal Cancer Patients with Diabetes Mellitus II - Yaodu Wang; Zhiyang Wu; Likuan Hu (Gastroenterology Research and Practice)
Objectives. We aimed to explore the association between metformin treatment and epithelial-mesenchymal transition (EMT) phenotype and further appraise the prognostic values of metformin and EMT markers E-cadherin and vimentin for colorectal cancer (CRC) in clinical practice. Methods. We collected specimens and evaluated clinicopathological parameters of 102 stage I to III CRC patients with prediagnosed type 2 diabetes mellitus (DM II). Expression of E-cadherin and vimentin in tumors was detected by immunohistochemistry (IHC), and statistical analysis was performed using SPSS 19.0. Results. In correlation tests, we found a lower tumor cell EMT degree (more E-cadherin (P=0.014) and less vimentin (P=0.011) expression in patients who used metformin, and the expression of E-cadherin and vimentin was associated with serum CA19-9 (P=0.048, P=0.009), tumor invasive depth (T) (P<0.001, P=0.045), and lymph invasion (N) (P=0.013, P=0.001). In Cox multivariate regression analysis, E-cadherin was identified as a prognostic factor for disease-free survival (DFS) (P=0.038) and metformin use (P=0.015P=0.044) and lymph invasion (P=0.016P=0.023) were considered as the prognostic factors for both DFS and overall survival (OS). Conclusion. Our study suggested that metformin may impede the EMT process and improve survival for stage I–III CRC patients with DM II.